Cooperative adaptive fault-tolerant control for heterogeneous multiagent systems with guaranteed performance - Jianye Gong; Xiuli Wang; Yang Li; Dandan Lyu (Artificial Intelligence and Autonomous Systems)
This paper studies the fault-tolerant control problem for the heterogeneous multiagen systems consisting of multiple quadrotors and mobile robots with guaranteed performance in the presence of unknown actuator faults. First, the full-state performance constraints of the position and attitude subsystem of follower vehicles are considered, especially in the case of actuator faults, and then the state constraints of heterogeneous unmanned systems are addressed by combining the performance functions and barrier Lyapunov function method. Then, the constraints-based cooperative adaptive fault-tolerant control strategy is proposed, where the adaptive terms are adopted to compensate for the unknown bounded actuator loss of effectiveness faults and bias faults and the constraint signals are introduced to ensure the performance conditions of system states. Based on the theoretical analysis, the cooperative fault-tolerant time-varying formation convergence performance is discussed. The simulation results on the UAVs-UGVs formation systems composed of quadrotors and mobile robots are presented to validate the effectiveness of the proposed control strategy.